A Systematic Literature Review on Ambush Marketing in Sport - Piątkowska Monika; Żyśko Jolanta; Gocłowska Sylwia (Sciendo, 2015)
The aim of the paper was to outline and evaluate the existing scientific achievements regarding the phenomenon of ambush marketing in sport, mark the dominating problematic areas, and create a literature database for the purposes of further research. The systematic literature review was conducted in the following stages: planning and conducting the review, analysis, and description of the results. The preliminary analysis included a combined number of 21,176 studies published between 1984-2013 in journals, books, and other sources included in analyzed databases, chosen using a meta-keyword: ambush. Analysis of the subject literature on the phenomenon of ambush marketing in sport allows for the classification of the works into three dominating research areas: identification of ambush marketing phenomenon, identification of the influence of ambush marketing practices on consumers, and identification of counter-ambush strategies. This review indicates the need for secondary research in social sciences in a more systematic way and more rigorously than it was done until now.